A redox cascade of NOx− complexes: Structures and nitrogen deoxygenation thermodynamics. (15th May 2021) - Cabelof, Alyssa C.; Erny, Alec M.; Beagan, Daniel M.; Caulton, Kenneth G.
Graphical abstract: A computational investigation of pincer manganese complexes bearing nitrogen oxyanions is reported. Investigation of thermodynamic preferences of isomers as well as thermodynamics of deoxygenation reveal favorable energetics for deoxygenation processes. Abstract: The pincer ligand PNNH contains pyridine with its ortho carbons bearing one tBu2 PCH2 donor and one pyrazole donor. A DFT study of the energies and structures of (PNNH)Mn(CO)n (NOx ) (n = 0–2, x = 0–3) reveals thermodynamic preferences over the suite of compounds. In every NOx case, the cis positioning of two carbonyls gives a more stable isomer than does the trans, which is understood as avoiding the trans conflict of two strong π acid ligands. The calculations also reveal a preference for nitrito (ONO) linkage isomers over the nitro (NO2 ) alternative. Additionally, the calculations predict loss of one CO when the nitrosyl oxidation level is reached, forming the five-coordinate (PNNH)Mn(CO)(NO). Nitrosyl ligand bending is evaluated with changing manganese coordination number, and diagnostic infrared frequencies are also discussed. We also investigate the thermodynamics of deoxygenation of the original coordinated nitrate. It is shown that reductive deoxygenations among these species are thermodynamically favored using a bis silyl dihydropyridazine reagent (oxygen removed as O(SiMe3 )2 ).